2022
DOI: 10.26633/rpsp.2022.3
|View full text |Cite
|
Sign up to set email alerts
|

Esfuerzos realizados en Puerto Rico hacia la consolidación de políticas públicas para la prevención de cánceres asociados al VPH

Abstract: El propósito de este informe especial es describir cronológicamente los eventos que contribuyeron al desarrollo y aprobación de la legislación e implementación del requisito escolar de vacunación en Puerto Rico (PR), con el fin de prevenir el VPH y los cánceres asociados a este. A partir del 2010, PR inició las aprobaciones de políticas públicas con el objetivo de mejorar el registro de casos de los cánceres y la cobertura de la vacuna contra el VPH a través de los planes médicos en adolescentes de 11 a 18 año… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In our study, we found -as expected- that most participants knew about COVID vaccines. Also, participants reported a higher level of COVID vaccine knowledge than for the HPV vaccine, even though, HPV vaccines have been accessible since 2006 in the USA and PR, 6 and HPV vaccination has been a school entry requirement in PR since 2018. Thus, the impact of the COVID pandemic has led to higher public perceived knowledge and promotion of the COVID vaccine, in contrast to HPV vaccines, for which education efforts have targeted a specific age group (9 to 26 years old)—the individuals who benefit the most from the vaccine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, we found -as expected- that most participants knew about COVID vaccines. Also, participants reported a higher level of COVID vaccine knowledge than for the HPV vaccine, even though, HPV vaccines have been accessible since 2006 in the USA and PR, 6 and HPV vaccination has been a school entry requirement in PR since 2018. Thus, the impact of the COVID pandemic has led to higher public perceived knowledge and promotion of the COVID vaccine, in contrast to HPV vaccines, for which education efforts have targeted a specific age group (9 to 26 years old)—the individuals who benefit the most from the vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…This law was later expanded in 2012 to include boys. 6 Most recently, on August 2018, the PR Secretary of Health added the HPV vaccine to the list of required vaccines for school entrance among children aged 11 and 12 years. 7 In the 2019–2020 academic period, the school HPV vaccine requirement was expanded to children between 11 to 14 years old and later broadened its reach in 2020–2021 to students up to 16 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address low HPV vaccination coverage rates, five states and territories/jurisdictions in the U.S. have adopted a school-entry requirement for HPV vaccine (Virginia in 2008; the District of Columbia in 2009; Rhode Island in 2015; Puerto Rico (PR) in 2018 and Hawaii in 2020) [14][15][16]. The efforts made to implement the policy in Puerto Rico and how it was enacted can be found elsewhere [17,18]. However, policies in these five states/territories are different [19].…”
Section: Introductionmentioning
confidence: 99%